DEVELOPING AND VALIDATING EFL READING TEST - Anugrah Novendi Perkasa (EDUCAFL : Journal of Education of English as Foreign Language, 2021)
EFL students need to learn about reading comprehension because, it is one of the essential abilities in learning English. To measure the students reading comprehension, a reading test is needed. Nevertheless, many students find difficulties in working the reading test. It happens because the reading tests which are given by teachers who do not analyze item difficulty, discrimination, distractor, and reliability. Those analyses are needed to prove that the reading test has met criteria of good tests. Criteria of good tests are needed in making the reading test because the reading test is used for measuring the achievement of EFL students. This study purposes at developing the reading test based on Indonesia National Curriculum basic competence, learning indicators, English lessons, and it examines to meet the criteria of good test. The researcher adapted Borg and Gall's (1983) theory in developing the reading test.